Ferromagnetic copper-doped ZnO for spintronics - Herng, Tun Seng (2008)
Intensive research is being carried out in copper-doped ZnO (ZnO:Cu) to study the underlying physics and physical origin of room temperature ferromagnetism in ZnO:Cu system. A series of ZnO:Cu films were prepared by filtered cathodic vacuum arc (FCVA) technique and the magnetic properties of the samples were studied as a function of deposition temperature and Cu concentration. The magnetic moment of ~0.4 uB/Cu was obtained for the room temperature deposited films having a Cu concentration of ~1 at.%. The presence of Zn interstitials, Cu and magnetic polaron in the films are related to the ferromagnetic ordering in the ZnO:Cu samples. The incorporation of N increases the substitution of high spin state of Cu2+ concentration into Zn2+ sites and stabilizes the highly diffusive Zni through N-Zn bonding. The flexible ZnO:Cu on plastic substrate and ZnO:Cu nanoneedles have been demonstrated. The magnetic anisotropy of ZnO:Cu nanoneendles at high magnetic field is related to the distribution of Cu2+ and defect density. Several heterostructures LEDs have been fabricated using the ZnO:Cu as an electron injector and a p-type GaN as hole injector. Electroluminescent from these LEDs can be detected.